EST-SSR development for Digitaria exilis and its relatives D. iburua and D. longiflora from transcriptome sequences - Olodo, K.F.; Gueye, M.C.; Calatayud, C.; Diop, B.M.; Kane, N.A.; Ngom, A.; Ntui, V.O.; Barreto, M.M.S.; Uyoh, E.A.; Abraham, S.; Vigouroux, Yves; Billot, C.; et al. (Cambridge University Press, 2018)
Digitaria exilis is an important indigenous cereal in West Africa. The first fonio reference transcriptome was released and became a key tool for developing new molecular markers contributing to a better understanding of its genetic diversity. A total of 126 new putative primer pairs were successfully designed in 37,327 unigenes from the D. exilis transcriptome. Thirty-seven primer pairs were randomly selected and tested for their ability to cross-amplify to related species. Clear amplification patterns were observed on 24 primer pairs. Of these, 71, 74 and 35% showed polymorphism in three species: D. exilis, D. longiflora and D. iburua. The transferability from D. exilis was 96% to D. longiflora and 71% to D. iburua. The new SSR markers confirmed the close genetic proximity of D. exilis with D. longiflora and its stronger genetic difference of D. exilis from D. iburua. These markers will be valuable for completing future knowledge on Digitaria evolutionary history, and for testing gene flows between related species.